P056 Methodology and Initial Results From TOUR (Tofacitinib Response in Ulcerative Colitis): A Real World Prospective Multicenter Study. (December 2019) - Long, Millie; Abdalla, Maisa; McCabe, Robert; Fischer, Monika; Cohen, Benjamin; Afzali, Anita; Polyak, Steven; Hanson, John; Herfarth, Hans
Abstract : BACKGROUND: Tofacitinib is a janus kinase (JAK) inhibitor approved for use in ulcerative colitis (UC) in 2018. Prospective real-world data on tofacitinib use in UC patients are limited. We aimed to develop a unique electronic system to obtain patient reported outcomes (PROs) from patients initiating tofacitinib. We aimed to measure response to therapy on days 1-14, anxiety, depression and social satisfaction. METHODS: An initial sample of 23 patients were recruited from 8 academic and community gastroenterology practices. Complete demographic information, disease and medication histories were obtained. Patients completed PRO surveys on days 1-14 after initiation of tofacitinib via a unique electronic self-report system. Outcome data included the simple clinical colitis activity index (SCCAI), and PRO measurement information system (PROMIS) measures of depression, anxiety and social satisfaction. A score of ⩽2 on SCCAI was considered to be remission; a score of <4 with a decrease by > 1.5 points was considered to be response. PROMIS measures were calibrated using a T score metric with the mean of the standard US population equal to 50, standard deviation (SD) of 10. A higher PROMIS score equates to more of the measure (higher scores worse for depression, anxiety and higher scores better for social satisfaction). RESULTS: A total of 23/23 (100%) completed electronic PRO data daily in the first 14 days after initiation of tofacitinib. Mean age of the population was 40.7 (SD 18.1), 56.5% were male, mean disease duration was 11.3 years and 73.9% were on concomitant steroids. Mean disease activity at baseline (n = 23) was active (SCCAI of 4.0), with reductions in mean daily disease activity to a nadir of SCCAI 2.2 on day 14. Among patients initiating tofacitinib without concomitant corticosteroid use (n = 6), similar early reductions in SCCAI were seen (mean SCCAI 4.0 at baseline, reduced to 1.8 by day 4). Improvements in all PROMIS measures (anxiety, depression, social satisfaction) were seen in the population by day 7. A total of 8/12 (66.7%) with active disease at baseline met criteria for response at day 14. CONCLUSION(S): Real time electronic PRO data capture directly from UC patients is feasible. This ongoing prospective multi-center real-world cohort demonstrated an excellent patient adherence to the online platform in the first 14 days. Initial data suggest a rapid response to tofacitinib in this sample, with improvements in disease activity, depression, anxiety and social satisfaction. Continued enrollment and long-term follow-up data from this cohort will enhance our knowledge of tofacitinib use in real world UC populations.